Bone Mineral Density in Patients with Ankylosing Spondylitis - Özlem Altındağ,; Mehmet Karakoç,; Neslihan Soran,; Hasan Tabur,; Ahmet Demirkol, (Archives of Rheumatology, 2008)
Objective: Patients with inflammatory arthritis are at risk for osteoporosis and bone fractures. Inflammation and immobility contribute to bone loss in patients with ankylosing spondylitis (AS). The aim of this study was to determine bone mineral density (BMD) in patients with AS, and to compare the data of the AS patients with matched healthy controls. In addition, we sought to determine whether BMD values are related to disease activity in patients with AS or not. Patients and Methods: BMD measurements were performed with the use of Dual-Energy X-Ray Absorptiometry (DXA) in 62 AS patients and 36 healthy controls. BMD was measured in spine L2-4 (anterior-posterior view) and femoral neck by DXA. Results: The study showed that patients with AS have lower BMD values and t scores than healthy controls (p<0.001). Furthermore, total lomber BMD value negatively correlated with the length of disease duration in patients with AS (r=-0.322, p =0.01). Conclusion: We thought that evaluation and treatment of osteoporosis was helpful in especially late stages of AS . (Rheumatism 2008; 23: 42-5)